Dimensi Budaya Keselamatan Pasien dan Insiden Keselamatan Pasien di RS X Kota Malang - Elystia Vidia Marselina; Hadi Prayitno; Ketut Ima Ismara (FORIKES, 2023)
Patient safety culture is a contributing factor to organization and management in implementing patient safety programs. The purpose of this study was to determine the effect of 12 dimensions of patient safety culture on patient safety incidents. This research was a quantitative study with a cross-sectional design. Respondents were selected by simple random sampling technique, namely 109 nurses at RS X Malang City. The data collection instrument was the Hospital Survey On Patient Safety Culture issued by AHRQ (Agency for Healthcare Research and Quality). The data analysis method used was multiple linear regression test. The results of the analysis showed that the p-value for the dimensions of overall perception of patient safety = 0.000, communication openness = 0.035, feedback and communication about errors = 0.041, incident reporting frequency = 0.000, handover and transition = 0.014, staffing = 0.008, cooperation between units = 0.000, cooperation within the unit = 0.000, and the expectations and actions of supervisors/managers in promoting patient safety = 0.000. This study reveals that the dimensions of patient safety culture influence patient safety incidents. Effectiveness in evaluating patient safety culture must be linked to strategies designed to develop an overall patient safety culture in Hospital X.Keywords: organization; patient safety culture; patient safety incident ABSTRAK Budaya keselamatan pasien merupakan faktor kontributor dari organisasi dan manajemen, dalam upaya penerapan program keselamatan pasien. Tujuan penelitian ini adalah untuk mengetahui pengaruh 12 dimensi budaya keselamatan pasien terhadap insiden keselamatan pasien. Penelitian ini merupakan penelitian kuantitatif dengan rancangan cross-sectional. Responden dipilih dengan teknik simple random sampling, yakni 109 perawat di RS X Kota Malang. Instrumen pengumpulan data adalah Hospital Survey On Patient Safety Culture yang dikeluarkan oleh AHRQ (Agency for Healthcare Research and Quality). Metode analisis data yang digunakan adalah uji regresi linier ganda. Hasil analisis menunjukkan bahwa nilai p untuk dimensi persepsi keseluruhan tentang keselamatan pasien = 0,000, keterbukaan komunikasi = 0,035, umpan balik dan komunikasi tentang kesalahan = 0,041, frekuensi pelaporan kejadian = 0,000, serah terima dan transisi = 0,014, staffing = 0,008, kerjasama antar unit = 0,000, kerjasama dalam unit = 0,000, dan ekspektasi dan tindakan supervisor/manajer dalam mempromosikan keselamatan pasien = 0,000. Penelitian ini mengungkapkan bahwa dimensi budaya keselamatan pasien berpengaruh terhadap insiden keselamatan pasien. Keefektifan dalam mengevaluasi budaya keselamatan pasien harus dikaitkan dengan strategi yang dirancang untuk mengembangkan budaya keselamatan pasien secara menyeluruh di RS X.Kata kunci: organisasi; budaya keselamatan pasien; insiden keselamatan pasien